Pendidikan Moral sebagai Pendidikan Islam (Ditinjau dalam Perspectif Islam) - Abd Hakim (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2020)
Moral education becomes the foundation in Islamic education to be able to develop and advance in the current era. Indonesia is one of the countries with the largest Muslim majority in the world so that in its development this moral education is important as a good Islamic education for the nation's generation. In this modern era, the problems that occur today are not only a lack of moral education in Indonesia, but also a lack of Islamic education so that these problems also develop together. This research uses qualitative research methods with literature study with descriptive-analytical research type so that in conducting research it will rely on articles, books, journals and other relevant news. In dealing with the problem of moral education, there are various things that must be studied, such as the improvement of morals and morals that originate from the al-Qur'an and hadiths so that this generation has a strong faith and Islam. In addition, improving technology and information is one of the most important things. Based on the Islamic perspective, it is considered that the younger generation is not only decreasing in moral awareness, but has a good character.